Remotely Guided Immunobots Engaged in Anti‐Tumorigenic Phenotypes for Targeted Cancer Immunotherapy. Issue 46 (6th October 2022) - Dogan, Nihal Olcay; Ceylan, Hakan; Suadiye, Eylül; Sheehan, Devin; Aydin, Asli; Yasa, Immihan Ceren; Wild, Anna‐Maria; Richter, Gunther; Sitti, Metin
Abstract: Building medical microrobots from the body's own cells may circumvent the biocompatibility concern and hence presents more potential in clinical applications to improve the possibility of escaping from the host defense mechanism. More importantly, live cells can enable therapeutically relevant functions with significantly higher efficiency than synthetic systems. Here, live immune cell‐derived microrobots from macrophages,  i.e.,   immunobots, which can be remotely steered with externally applied magnetic fields and directed toward anti‐tumorigenic (M1) phenotypes, are presented. Macrophages engulf the engineered  magnetic decoy bacteria, composed of 0.5 µm diameter silica Janus particles with one side coated with anisotropic FePt magnetic nanofilm and the other side coated with bacterial lipopolysaccharide (LPS). This study demonstrates the torque‐based surface rolling locomotion of the immunobots along assigned trajectories inside blood plasma, over a layer of endothelial cells, and under physiologically relevant flow rates. The immunobots secrete signature M1 cytokines, IL‐12 p40, TNF‐α, and IL‐6, and M1 cell markers, CD80 and iNOS, via toll‐like receptor 4 (TLR4)‐mediated stimulation with bacterial LPS. The immunobots exhibit anticancer activity against urinary bladder cancer cells. This study further demonstrates such immunobots from freshly isolated primary bone marrow‐derived macrophages since patient‐derivable macrophages may have a strong clinical potential for future cell therapies in cancer. Abstract : Live immune cell‐derived microrobots from macrophages, i.e., immunobots, combine robotic mobility control and immunomodulatory functions on immune cells: i) stimulating and sustaining macrophages toward the anti‐tumorigenic phenotypes and ii) controlling their direction of rolling motion precisely using an external magnetic field. The immunobot fabrication process is highly efficient (≈99.2%) and maintains durable anti‐tumorigenic phenotypes, where the immunobots exhibit significant anticancer activity in mouse urinary bladder cancer cells.